Predictors of functional capacity as measured by the Glittre activities of daily living test in women with rheumatoid arthritis - Palugan,M.J.A. (2021)
Although pulmonary involvement is the most common extra-articular manifestation of rheumatoid arthritis (RA), traditional pulmonary function tests (PFTs) do not show a good correlation with the field tests usually performed in these patients. In recent decades, measurement of ventilation distribution heterogeneity through the nitrogen single-breath washout (N2SBW) test and evaluation of functional capacity during exercise using the Glittre activities of daily living test (GA-T) have been increasingly used. Therefore, the objective of this study was to evaluate predictors of GA-T outcomes in women with RA considering demographic, anthropometric, clinical, functional variables, and chest computed tomography (CT) findings. Forty-three women with RA underwent the GA-T, the N2SBW test, spirometry, measurement of the diffusing capacity for carbon monoxide (DLco), measurement of respiratory muscle strength, and evaluation of physical function of the lower and upper limbs through the Health Assessment Questionnaire Disability Index (HAQ-DI). Chest CT scans were analyzed retrospectively. The GA-T time showed significant correlations with the DLco (rs=-0.397, P=0.008), forced vital capacity/DLco (rs=0.307, P=0.044), phase III slope of the N2SBW test (SIIIN2, rs=0.644, P<0.0001), and the HAQ-DI (rs=0.482, P=0.001). Disease extent as assessed by chest CT was associated with the GA-T time. On multiple regression analysis, the SIIIN2 and HAQ-DI were the only predictors of the GA-T time, explaining 40% of its variability. Thus, ventilation distribution heterogeneity and worse physical function substantially explain the variability in GA-T time in women with RA and varying extents of disease on chest CT.